Optimization of Fungal Decolorization of Isolan Grey using Plackett-Burman Experimental Design - Hema N.; Suresha S. (International Journal of Research in Chemistry and Environment (IJRCE), 2015)
Penicillium oxalicum RF3 isolated from textile dye effluent was evaluated for its ability to decolorize the metal complex dye Isolan grey. Percentage decolorization of the dye by fungi was taken as the response to screen and optimize the media constituents using statistically valid Plackett-Burman and response surface methodology (RSM) design of experiments, respectively. The significance of the factors was analysed in the form of ANOVA, in which Inoculum size showed significant effect on dye decolorization. Ammonium chloride showed suggestive significance indicating its importance in dye decolorization. Response surface methodology used in optimizing the important media constituents for enhancing the decolorization of Isolan grey, revealed optimum combinations of all factors which gave maximum percent dye decolorization of 50.75% with Inoculum size=29.28%, Fructose=0.67%, Urea=0.21%, Lactose=0.021%, K2HPO4=0.44%, NH4Cl=0.54%, MgSO4=0.60% with pH 7, temperature 25°C, dye concentration 0.01% and incubation duration=120 hours. The pareto chart plotted for all seven factors indicated that inoculum size, fructose, NH4Cl and K2HPO4 positively influenced the dye decolorization process. The degradation of Isolan grey into different metabolites by the isolate was confirmed using Fourier transform infrared spectroscopy. These results suggest that the isolated fungus is suitable for the biological treatment of dye-containing wastewater.